2004
DOI: 10.1080/02652030410001687717
|View full text |Cite
|
Sign up to set email alerts
|

Presence and metabolism of the anabolic steroid boldenone in various animal species: a review

Abstract: The review summarizes current knowledge on the possible illegal use of the anabolic steroid boldenone. The presence of' boldenone and metabolites in different animal species and the possibility of the occurrence of endogenous boldenone and metabolites is assessed, as are the methods of analysis used for detection. Different laboratories in the European Union have examined the occurrence of boldenone and its metabolites. The results were discussed at different meetings of a European Commission DG-SANCO Working … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
71
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 26 publications
3
71
0
4
Order By: Relevance
“…The authors attributed the high concentrations of 17-boldenone ( BOL), 1,4-androstadiene-3,17-dione (ADD) and, in some samples, of 17-boldenone ( BOL) present in slaughterhouse faeces, to oral administration of BOL esters or precursors. More recently, Nielen et al (2004) found BOL (520.0 ng/g) and BOL (21.0 ng/g) in dried faeces from calves reported to be untreated; Sangiorgi et al (2005) detected these substances in rectal faeces from untreated calves, while De Brabander et al (2004) reported low concentrations of BOL and (1->10 ng/g) and BOL (0.1-2.0 ng/g) in faeces scraped off the skin of calves. It therefore seems that and BOL can be present in a wide range of concentrations in faecal materials sampled outside the animals.…”
Section: Introductionmentioning
confidence: 99%
“…The authors attributed the high concentrations of 17-boldenone ( BOL), 1,4-androstadiene-3,17-dione (ADD) and, in some samples, of 17-boldenone ( BOL) present in slaughterhouse faeces, to oral administration of BOL esters or precursors. More recently, Nielen et al (2004) found BOL (520.0 ng/g) and BOL (21.0 ng/g) in dried faeces from calves reported to be untreated; Sangiorgi et al (2005) detected these substances in rectal faeces from untreated calves, while De Brabander et al (2004) reported low concentrations of BOL and (1->10 ng/g) and BOL (0.1-2.0 ng/g) in faeces scraped off the skin of calves. It therefore seems that and BOL can be present in a wide range of concentrations in faecal materials sampled outside the animals.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, like the other androgenic steroids, 17β-BOL is classified by the International Agency for Research on Cancer (IARC) in class 2A (growth promoters -steroids), as a probable human carcinogen (e.g. prostate and liver tumors), with a carcinogenicity index higher than that of other androgens, such as nandrolone, stanozolol and testosterone [7]. A recent study has demonstrated the role of 17α-BOL in the d e v e l o p m e n t o f h u m a n p r o s t a t e c a r c i n o m a s xenotransplanted into nude mice [3].…”
mentioning
confidence: 99%
“…To prevent the abuse of anabolics in animal production, biological samples, including urine, blood and hair, are periodically taken from selected farms. Existing literature relates the presence in the urine samples of BOL and ADD derivatives, like 17α-BOL and 17β-BOL conjugates, to proof of illegal treatment [7], while the presence of 17α-BOL free in urine and faeces of animal species can come from resources other than illegal treatment [18], like phytosterols in food [19]. Since no clear correlation has yet been found between different observations, studies are being carried out in order to better understand the significance of these metabolites in urine and faeces of cattle [7].…”
mentioning
confidence: 99%
See 2 more Smart Citations